Epidemiology of Carbapenem-Resistant Enterobacterales Infection and Colonization in Hospitalized Patients at a University Hospital in Thailand - Walaiporn Wangchinda (2022)
Purpose: To investigate the epidemiology of carbapenem-resistant Enterobacterales (CRE) colonization or CRE infection relative to the natural history and clinical course of CRE colonization or CRE infection in hospitalized patients during admission and after discharge. Material and Methods: Two adult cohorts were enrolled. Cohort I comprised hospitalized patients who had CRE isolated from their clinical specimens during 2018–2020. CRE colonization or CRE infection was based on the absence/presence of clinical features of infection. Information regarding the natural history and clinical course of these patients was collected during hospitalization. Stool samples were evaluated for CRE once a week during hospitalization, and then once every few months after discharge until negative for CRE. Cohort II comprised patients who had CRE isolated from clinical specimens during hospitalization and who were discharged during 2015–2018. CRE in stool samples collected from these patients every few months was assessed to determine duration of CRE in stool. Results: CRE in stool was detected in 69.7% of 353 patients in cohort I. K. pneumoniae was the predominant CRE isolated from clinical samples (76.8%) and stool samples (65.7%). Among the 225 CRE-colonized patients, 20.4% developed subsequent CRE infections with a median duration from CRE colonization to CRE infection of 14 days. Among 174 CRE-infected patients, the most common infection was pneumonia with mortality at discharge of 47.7%. Duration of CRE colonization in stool was <1 year in 50.0% of cohort I patients, and <2 years in 91.4% of patients in cohort II. Conclusion: CRE isolated from clinical specimens in hospitalized patients are more likely to cause colonization than infection. Patients with CRE colonization are at risk of subsequent CRE infection with high mortality. Stool culture for CRE is needed to verify if contact precautions can be discontinued because the duration of CRE colonization in stool varied from days to years.